2020
DOI: 10.1002/pol.20200204
|View full text |Cite
|
Sign up to set email alerts
|

Target grafting of poly(2‐(dimethylamino)ethyl methacrylate) to biodegradable block copolymers

Abstract: A series of copolymers composed of methoxy poly(ethylene glycol) and a hydrophobic block of poly(ɛ‐caprolactone‐co‐propargyl carbonate) grafted with poly(2‐[dimethylamino]ethyl methacrylate) was synthesized by combining ring opening polymerization, azide‐alkyne click reaction, and atom transfer radical polymerization (ATRP). Well‐defined copolymers with a target composition and a tailored structure were achieved via the grafting from approach by using a single catalytic system for both click reaction and ATRP.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Polymer stock solutions were prepared in sterile ultrapure PCR-water (Sigma-Aldrich) as 1.25 mg mL –1 (l-PEI) and 1.82 mg mL –1 (Nanostar) and diluted for use as indicated. LD 50 values were 12.1 μg mL –1 for l-PEI 66 and 500 μg mL –1 for Nanostar 11 as determined by MTT assay.…”
Section: Materials and Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Polymer stock solutions were prepared in sterile ultrapure PCR-water (Sigma-Aldrich) as 1.25 mg mL –1 (l-PEI) and 1.82 mg mL –1 (Nanostar) and diluted for use as indicated. LD 50 values were 12.1 μg mL –1 for l-PEI 66 and 500 μg mL –1 for Nanostar 11 as determined by MTT assay.…”
Section: Materials and Methodsmentioning
confidence: 98%
“…In the previous studies, we have investigated the physicochemical properties of these PPs and established the indicated N/P ratios as optimal for transfection with these polymers. 11 , 12 , 56 , 66 The mixture was vortexed for 10 s and incubated for 20 min at room temperature. Then, one volume of a 0.002% TB solution or a 2 μg mL –1 PI solution was added.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The better survival of the cells in case of transfection with l-PEI may also be ascribed to the lower polymer densities (6.0 to 39.0 µg per 10 6 cells for l-PEI, 22.0 to 144.0 µg per 10 6 cells for the nano-stars) and polymer concentrations (0.6 to 4.0 µg mL −1 for l-PEI, 2.0 to 14.0 µg mL −1 for the nano-stars) required to reach the indicated N/P ratios (see Table S1 for details). However, for both polycations, the polymer concentration at the highest N/P ratio was still below the LD 50 values recorded for free l-PEI (12 µg mL −1 ) and nano-stars (39 µg mL −1 ) in L929 cells (MTT assay) by our group [ 45 ]. Previously, we have shown that human primary T cells have a two-fold higher sensitivity to these polycations than the L929 cells and some similarity can be presumed for primary B cells [ 37 ].…”
Section: Resultsmentioning
confidence: 68%
“…This trend agreed with the results of previous reports for analogous materials. 20,23 The trend also indicate that the cellular viability is sensitive to the grafting density, as deduced from the LD 50 values obtained for the PP6Ly series.…”
Section: In Vitro Cytotoxicity Assaymentioning
confidence: 85%
“…The structure and composition of these materials were confirmed by 1 H NMR, as previously reported (Supplemental Figure S1). 23 Then, mPEG-b-P(CL-co-(MPC-g-lPEI)) copolymers were synthesized by grafting azideterminated lPEI (lPEI-N 3 ) to mPEG-b-P(CLco-MPC) backbones through the alkyne groups via click chemistry. First, lPEI-N 3 was obtained by the acidic hydrolysis of poly(2-methyl-2-oxazoline) α-benzyl ω-azide terminated (PMeOx-N3, M n ~5000) at 100°C using an excess of aqueous HCl.…”
Section: Synthesis Of Mpeg-b-p(cl-co-(mpc-g-lpei)) Copolymersmentioning
confidence: 99%